RISK UNIVERSITY: UNCERTAINTY OF THE LATE MODERNITY COMING TOO EARLY - DEUTSCHMANN, MARCIN; WANKE, MICHAŁ (Society Register, 2020)
The study examines how a regional university, having recently overseen a dramatic internationalization, deals with the consequences of COVID-19, and how the students - many of whom are international and coming from the global peripheries - experience the pandemic. The study is informed by the critical theory of late modernity and capitalism - especially the theory of uncertainty and risk (Beck, 1992; Beck, Giddens, & Lash 1994). It explores the power relations of the communicative dynamic between the administrators managing the crisis and the students perceiving and living it. It is an early-stage research report, published days after a pilot study was run. A survey among international students (including local, tuition-fee paying, and exchange students) was distributed to obtain initial responses. The analysis is complemented by insights based on close observation of the unfolding situation and analysis of the documents issued by the university. The findings explain the uncertainty experienced by international students, characteristic of many CE universities. The study covers the topics of attitudes towards epidemics, information imbalance, perception of security, and evaluation of the responses. The paper concludes with an urgent call to recently internationalized universities for a recognition of the complexity of students’ fears.